Parkinsonism in fragile X-associated tremor/ataxia syndrome (FXTAS): Revisited - Niu, Yu-Qiong (2014)
BACKGROUND: Parkinsonian features have been used as a minor diagnostic criterion for fragile X-associated tremor/ataxia syndrome (FXTAS). However, prior studies have examined parkinsonism (defined as having bradykinesia with at least rest tremor or postural instability) mostly in premutation carriers without a diagnosis of FXTAS. The current study was intended to elaborate this important aspect of the FXTAS spectrum, and to quantify the relationships between parkinsonism, FXTAS clinical staging and genetic/molecular measures. METHODS: Thirty eight (38) FXTAS patients and 10 age-matched normal controls underwent a detailed neurological examination that included all but one item (i.e. rigidity) of the motor section of the Unified Parkinson’s Disease Rating Scale (UPDRS). RESULTS: The FXTAS patient group displayed substantially higher prevalence of parkinsonian features including body bradykinesia (57%) and rest tremor (26%), compared to the control group. Furthermore, parkinsonism was identified in 29% of FXTAS patients. Across all patients, body bradykinesia scores significantly correlated with FXTAS clinical stage, FMR1 mRNA level, and ataxic gait of cerebellar origin, while postural instability was associated with intention tremor. INTERPRETATION: Parkinsonian features in FXTAS appear to be characterized as bradykinesia concurrent with cerebellar gait ataxia, postural instability accompanied by intention tremor, and frequent rest tremor, representing distinctive patterns that highlight the need for further clinical studies including genetic testing for the FMR1 premutation. The association between FMR1 mRNA level and bradykinesia implicates pathophysiological mechanisms which may link FMR1 mRNA toxicity, dopamine deficiency and parkinsonism in FXTAS.